Comorbid conditions in lichen planopilaris: A retrospective data analysis of 334 patients - N. Brankov; R.Z. Conic; N. Atanaskova-Mesinkovska; M Piliang; W.F. Bergfeld (Wolters Kluwer, 2018)
Background: Lichen planopilaris (LPP) is a rare, cicatricial, lymphocyte-mediated alopecia that is thought to have an autoimmune pathogenesis and possibly related to other autoimmune diseases. However, data are limited and studies that examine comorbid conditions are lacking. Objectives: We sought to determine the prevalence of systemic comorbid conditions, nutritional deficiencies, psychological problems, and skin cancers in patients with LPP. Methods: We identified 334 patients with LPP who were seen in the Department of Dermatology at the Cleveland Clinic Foundation between 2000 and 2016. Patients with LPP were compared with 78 control patients with a diagnosis of seborrheic dermatitis. Results: There were more female patients with LPP compared with the controls (93.1% vs. 79.5%; p < .001) but the average age did not differ (54.77±12.83 vs. 52.19±15.37; p = .12). Conditions positively associated with LPP were Hashimoto's thyroiditis (6.3% vs. 0%; p = .023), hypothyroidism (24.3% vs. 12.8%; p = .028), and hirsutism (11.4% vs. 1.3%; p = .006). Negatively associated conditions were allergic rhinitis (15% vs. 24.4%; p = .046), diabetes mellitus type II (11.7% vs. 21.8%; p = .019), hyperlipidemia (38.6% vs. 52.6%; p = .024), vitamin D deficiency (50% vs. 65.4%; p = .014), depression (15.6% vs. 28.9%; p = .018), and sleep problems (7.5% vs. 29.5%; p < .001). Conclusions: Our study further emphasizes that dermatologists should screen patients with LPP for autoimmune disorders that are associated with LPP and complete a full metabolic workup to avoid missing other abnormalities. The importance of atopy, autoimmune disorders, endocrine disorders, nutritional deficiencies, psychological problems, and skin cancers in patients with scarring alopecia should be better understood. Keywords: alopecia, cicatricial alopecia, lichen planopilaris, comorbidities